Vloga tiskanih medijev pri prikazovanju slovenskih narodnih manjšin - Grafenauer, Danijel (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2013)
The presence and image of minorities in mass media are amongst the key issues relating to the promotion of the concept of the common Slovenian cultural territory and to present-day multiethnic societies in general. It is an established fact that mass media convey national symbols and promote ethnic identification. There is no typical media image of ethnic or national minorities in the Slovenian media territory. The attention of media is mostly focused on political problems, tensions and conflicts, as well as on events and individuals, who due to their greater social and cultural capital are more successful in subsidizing information for mass media. Events taking place in across-the-border culture, economy and sports are considerably less present in the main Slovene media. It is evident that such news are not fully used despite new technological options (of website media e.g.). The flow of information between neighbouring states and central Slovenia has partly improved over the recent years and is reflected in the reporting of RTVS, some other media and individuals.
Keywords: communication medium; mediji; tiskani mediji; narodne manjšine; zamejski Slovenci; Italija; Italy; Austria; Avstrija; Madžarska; Hungary; enotni slovenski kulturni prostor; čezmejno medijsko komuniciranje